Development of Crisis Phenomena in Social and Economic Systems in Conditions of Globalization - Nikolaevna Drobysheva, Nataliya; Petrovna Zvyagintseva, Elena; Alekseevna Fedorova, Elena; Aleksandrovna Kindrya, Nataliya; Evgenievna Lebedeva, Olga; ., . (International Journal of Engineering and Technology, 2018)
The article develops proposals for the systematization of crisis phenomena in socio-economic systems in the conditions of globalization. It was established that globalization only increases the frequency of crisis phenomena and their scale. It was proved that the strengthening of relations between individual countries predetermines the growth of their interdependence. It was determined that in the context of globalization, the economic entities of one country become dependent on the markets or resources of other countries. For the socioeconomic systems of an enterprise rank, the environment in modern conditions is often not the socioeconomic system of the higher rank, which includes the enterprise, but other socio-economic systems of higher rank. Therefore, the emergence of crisis situations is often considered in terms of the interaction of the socio-economic system of a certain level with the system of the higher level, considering the fact that the impact of crisis phenomena is the determining one.Â Â